Comparing the Correctness of Different Relations for Approximation of Retention Times in Reversed Phase HPLC with Methanol–Water Eluents - Derouiche Abdennour .Zenkevich ,Igor G (University of Eloued جامعة الوادي, 2024)
The correctness of different relations for approximating the retention times of selected analytes of different chemical origin in reversed phase high performance liquid chromatography (isocratic conditions, methanol–water eluents) is compared. Five equations most often used in analytical practice were considered: hyperbolic (Scott-Kuchera model), logarithmic (Soczewinski–Wachtmeister and Snyder–Soczewinski models), second degree polynomial, and recently proposed recurrent relations, tR(C + ΔC) = atR(C) + b, where tR is net retention time, and ΔC is the constant increment of the concentration of an organic modifier in an eluent. Two criteria for comparing the approximation quality were used. The first of them (known previously) is the maximal value of the correlation coefficient for the dependence tR(C); the second one is newly proposed. It implies hypothetical exclusion of the maximal and the minimal tR values from the total data set, followed by precalculation of these values using the remaining data and evaluation of the differences (tR – tR,calc) for both of them. The results obtained show that just recurrent relations provide the maximal precision of approximations compared to all the previously known approaches. In addition, the important advantage of recurrences is their applicability to net retention times without converting them to adjusted retention times
Article
Keywords: Reversed phase HPLC; Retention times; Different approximations; Recurrent regression